Release of Amino‐ or Carboxy‐Containing Compounds Triggered by HOCl: Application for Imaging and Drug Design. Issue 14 (6th March 2019) - Wei, Peng; Liu, Lingyan; Wen, Ying; Zhao, Guilong; Xue, Fengfeng; Yuan, Wei; Li, Ruohan; Zhong, Yaping; Zhang, Mengfan; Yi, Tao
Abstract: The overproduction of HOCl is highly correlated with diseases such as atherosclerosis, rheumatoid arthritis, and cancer. Whilst acting as a marker of these diseases, HOCl might also be used as an activator of prodrugs or drug delivery systems for the treatment of the corresponding disease. In this work, a new platform of HOCl probes has been developed that integrates detection, imaging, and therapeutic functions. The probes can detect HOCl, using both NIR emission and the naked eye in vitro, with high sensitivity and selectivity at ultralow concentrations (the detection limit is at the nanomolar level). Basal levels of HOCl can be imaged in HL‐60 cells without special stimulation. Moreover, the probes provided by this platform can rapidly release either amino‐ or carboxy‐containing compounds from prodrugs, during HOCl detection and imaging, to realize a therapeutic effect. Abstract : Triple action : An HOCl‐responsive platform has been developed that integrates detection, imaging, and therapeutic functions. The probes derived from this platform can detect HOCl by using NIR emission in vitro and in vivo with high sensitivity and selectivity. Additionally, they rapidly release amino‐ or carboxy‐containing compounds from prodrugs, during HOCl detection and imaging, to realize a therapeutic effect.